Pedagogical conditions of development of foreign language communicative competence of students - Anna L. Morozova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the theory and practice of the development of the foreign language communicative competence of students of non-linguistic areas of training in the implementation of the current Federal state educational standard of higher education (bachelor's and master's levels), implemented in the educational process of educational organizations subordinated to the Ministry of foreign affairs of the Russian Federation, in order to clarify the pedagogical conditions of the development of that competence. The educational and methodical pedagogical conditions presented by the author are aimed at the comprehensive development of foreign language communicative competence (to know, to be able, to own) of students, in accordance with the results of training (competencies) indicated in the analyzed Federal state educational standard of higher education. The question of the relevance of non-native language proficiency of students and graduates of non-language universities and their competitiveness in the modern domestic and foreign labor market is touched upon. This fact actualizes the development of the readiness of students studying in non-linguistic areas of training to use a foreign language for self-education in the course of training at the Institute and in subsequent professional activities.The tasks and content of the developed educational and methodical pedagogical conditions are considered. The question of the importance of the development of the content of education adequate to requirements of the current time on a subject "Foreign language" is brought up. The author specifies the actual methods of teaching that meet the requirements of the Federal state educational standard of higher education and competence approach: communicative, method of cases, method of projects, audio-linguistic, audiovisual, method of "Openwork saw", etc. Moreover, the requirements to the teaching staff working in the declared direction, for example: confident possession of the computer, the Internet, as well as distance learning technologies are given. The importance and structure of the funds of evaluation tools for the discipline aimed at identifying the real level of foreign language proficiency of students is explained. Evaluation funds allow the teacher to properly organize the educational process, and students to understand the requirements of the teacher.